Fish and Shellfish Diversity of Malam Beel, Bangladesh: Status, Trends, and Management Strategies - Mst. Jannatul Ferdous; Mst. Armina Sultana; Rasel Mia; Debasish Pandit; Mohd Golam Quader Khan; Md. Samsul Alam (Aquatic Sciences and Engineering)
Most of the waterbodies in Bangladesh's north-eastern haor basin have seen a gradual decline in their biodiversity, but little study has been done to determine their current condition. To address this issue, this research was conducted in the Malam beel under the Hakaluki haor – one of the largest wetland resources of the country. The study was conducted using a pre-tested questionnaire and a direct catch assessment survey in the beel. From 11 orders and 32 families, a total of 69 fish and shellfish species were identified. Of the species documented, 15.94% were classified as abundant, 39.13% were common, 27.54% were moderately available, and 17.39% were rare. Among the orders, Cypriniformes accounted for 37.68% of the total fish recorded. The most prevalent family was Cyprinidae found in Malam beel. Based on the findings, it can be concluded that Malam beel is a highly valuable inland open water body that has the potential to function as a key source of fishery resources as well as a gene bank for various fish species. However, some manmade and natural threats such as fishing by dewatering, brush pile fishing, illegal/destructive fishing and siltation were identified during the present study. Therefore, to ensure the sustainable maintenance of these water bodies, ecosystem-based fisheries management involving the local community is strongly advised.